HASIL PENGUJIAN SOFTWARE COMPUTERIZED ADAPTIVE TESTING (CAT) MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DALAM MEMBUAT REKAM MEDIK PEMBELAJARAN (RMP) UNTUK MENDIAGNOSIS KEMAMPUAN SISWA DI SEKOLAH - Winarno Winarno (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
This research aims at producing a Computerized Adaptive Testing (CAT) software Islamic religion education subject (CAT PAI) for the year 7 students of public junior high schoo and to see the results of CAT software in making rekam medik pembelajaran (RMP) to diagnose student’s ability. This research used the research and development approach. The data was collected by doing observation and documentation. Analyzedto use quantitative descriptive technique. The findings of the research shows the CAT can be developed web-based, and The CAT is able to in estimating student’s ability correct be seen RMP. Overall, the CAT software can perform the tasks well in order to select test items and to measure student’s ability from correlation value between ability estimation result (è) in CAT with Islamic religious education subjects enough tall that is 0,69.